2006
DOI: 10.1007/s00280-006-0327-1
|View full text |Cite
|
Sign up to set email alerts
|

The range of optimal concentration and mechanisms of paclitaxel in radio-enhancement in gastrointestinal cancer cell lines

Abstract: The range of optimal concentration for PXL pretreatment was 0.01-0.1 microM in these cells. Two major mechanisms of radio-enhancement are suggested: (1) PXL induces G2/M arrest leading to increased DNA damage after radiation, which results in mitotic death, and (2) PXL suppresses the expression of radiation-induced DNA repair molecules and angiogenesis factors, resulting in inhibition of cell growth and cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The values of minimum efficacious concentration and toxic concentration for paclitaxel used in the present work, c eff = 1 × 10 −5 mol m −3 and c tox = 1 × 10 −2 mol m −3 , are in agreement with [45]. These values are based on the work of [46] who studied the inhibitory effect of paclitaxel on cancer cells. This value of the minimum efficacious concentration is in good agreement with earlier work of [47], who reported prolonged inhibition of human arterial SMCs growth at a medium concentration of 1 × 10 −4 mol m −3 with an IC 50 value for paclitaxel on human arterial SMC growth of 2 × 10 −6 mol m −3 .…”
Section: Methodssupporting
confidence: 87%
“…The values of minimum efficacious concentration and toxic concentration for paclitaxel used in the present work, c eff = 1 × 10 −5 mol m −3 and c tox = 1 × 10 −2 mol m −3 , are in agreement with [45]. These values are based on the work of [46] who studied the inhibitory effect of paclitaxel on cancer cells. This value of the minimum efficacious concentration is in good agreement with earlier work of [47], who reported prolonged inhibition of human arterial SMCs growth at a medium concentration of 1 × 10 −4 mol m −3 with an IC 50 value for paclitaxel on human arterial SMC growth of 2 × 10 −6 mol m −3 .…”
Section: Methodssupporting
confidence: 87%
“…In addition to cisplatin, other chemotherapy drugs may interfere with ERCC1 expression. An in vitro study has shown that radiation activates ERCC1 expression in gastrointestinal cancer cell lines, but not in the same cell lines treated with paclitaxel prior to radiation, suggesting that paclitaxel may suppress ERCC1 (19). In a clinical study performed in ovarian cancer patients treated with cisplatin with or without paclitaxel (20), high levels of ERCC1 mRNA were associated with greater risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by the results of an in vitro experiment by Toiyama et al (40). Their research group has shown that radiations activate ERCC-1 expression in gastrointestinal cancer cells, but not in the same cells previously treated with paclitaxel, suggesting that paclitaxel blocks ERCC-1 activity, inhibits the DNA repair system and prevents cellular resistance to drug-induced DNA damage.…”
Section: Mthfr C677t Polymorphism and Methotrexatementioning
confidence: 68%